Spillover of an alien parasite reduces expression of costly behaviour in native host species. Issue 7 (14th April 2020) - Santicchia, Francesca; Wauters, Lucas A.; Piscitelli, Anna Pia; Van Dongen, Stefan; Martinoli, Adriano; Preatoni, Damiano; Romeo, Claudia; Ferrari, Nicola
Abstract: Understanding the effects of invasive alien species (IAS) on native host–parasite relationships is of importance for enhancing ecological theory and IAS management. When IAS and their parasite(s) invade a guild, the effects of interspecific resource competition and/or parasite‐mediated competition can alter existing native host–parasite relationships and the dependent biological traits such as native species' behaviour. We used a natural experiment of populations of native red squirrels Sciurus vulgaris that were colonized by the alien grey squirrel Sciurus carolinensis, comparing repeated measurements of red squirrel parasite infection and personality with those taken in sites where only the native species occurred. We explored two alternative hypotheses: (a) individual differences in personality traits (activity and/or sociability) of native red squirrel positively affect the probability of macroparasite spillover and thus the likelihood to acquire the alien's parasitic helminth Strongyloides robustus ; (b) the combined effects of grey squirrel presence and parasite infection result in a reduction of costly personality traits (activity and/or exploration). Using data from 323 arena tests across three experimental (native species and IAS) and three control sites (only native species), we found negative correlations between native species' activity and infection with S. robustus in the sites invaded by the alien species. Activity was also negatively correlated with infection by its native helminth Trypanoxyuris sciuri but only when grey squirrels were present, while in the red‐only sites there was no relationship of T. sciuri infection with any of the personality traits. Moreover, individuals that acquired S. robustus during the study reduced their activity after infection, while this was not the case for animals that remained uninfected. Our results show that parasite‐mediated competition is costly, reducing activity in individuals of the native species, and altering the native host–native parasite relationships. Abstract : The authors show how an alien parasite reduces the expression of activity, an energetically costly personality trait. The results also suggest that transmission of alien parasites may alter the native host–native parasite relationship: only in areas invaded by alien grey squirrels and their macroparasites, infection by the native oxiurid helminth reduced native hosts' activity.